Redescriptions of poorly known species of jumping spiders (Araneae: Salticidae) from South Africa and Namibia - Azarkina, Galina N.; Foord, Stefan H. (Zootaxa, 2013)
The following seven species of southern African Salticidae, known only from type specimens or one sex, and last described in the early 20th century, are redescribed: Baryphas ahenus Simon, 1902, Brancus muticus Simon, 1902, Euophrys quadrispinosa Lawrence, 1927, Evarcha natalica Simon, 1902, Mogrus macrocephalus Lawrence, 1927, Thyene damarensis Lawrence, 1927 and Thyene bilineata Lawrence, 1927. Two new synonyms are proposed, Thyene damarensis Lawrence, 1927 syn. n. with Hyllus dotatus (Peckham et Peckham, 1903) and Thyene bilineata striatipes Lawrence, 1927 syn. n. with T. bilineata Lawrence, 1927. One new combination is proposed, Thyenula natalica comb. n. (ex Evarcha). Lectotypes for Baryphas ahenus Simon, 1902 and Thyene bilineata Lawrence, 1927 are designated. The female of Brancus muticus Simon, 1902 is described for the first time.